2022
DOI: 10.20517/energymater.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium labelling by electrochemical splitting of heavy water

Abstract: Deuterium incorporation is crucial in organic synthesis and has wide applications in the pharmaceutical industry. State-of-the-art H/D isotope exchange and chemical defunctionalization for deuterium incorporation suffer from significant drawbacks, including expensive deuterium sources, low deuteration efficiency and poor selectivity. In this perspective, we highlight an alternative pathway for forming C-D bonds by electrocatalytic heavy water splitting (D2O) under mild conditions. In addition, the intrinsic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The drugs’ metabolism and pharmacokinetic properties will be profoundly modified by the presence of the deuterium (D) atom due to its kinetic isotope effect 1 6 . Since the first deuterated drug, deutetrabenazine (Austedo), has been approved by the US Food and Drug Administration (FDA) 7 , tremendous efforts have been devoted to synthesizing and patenting D-labeled pharmaceuticals 8 16 . Aryl ethylamines can serve as both important drug molecules and ubiquitous scaffolds in biologically active compounds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The drugs’ metabolism and pharmacokinetic properties will be profoundly modified by the presence of the deuterium (D) atom due to its kinetic isotope effect 1 6 . Since the first deuterated drug, deutetrabenazine (Austedo), has been approved by the US Food and Drug Administration (FDA) 7 , tremendous efforts have been devoted to synthesizing and patenting D-labeled pharmaceuticals 8 16 . Aryl ethylamines can serve as both important drug molecules and ubiquitous scaffolds in biologically active compounds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that the in situ generated H* (also called the hydrogen radical) via H 2 O electrolysis is responsible for the electrocatalytic hydrogenation reactions. The hydrogen radicals during hydrogenation of 1b are detected by the electron paramagnetic resonance (EPR) measurements and high-resolution mass spectrometry (HR-MS). The g -value and hyperfine coupling constants α N and α H are calculated as 2.0046, 16.3 G, and 22.4 G (Figure f), respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, electrocatalysis has gradually become an efficient and powerful tool in synthetic chemistry. Electrocatalytic hydrogenation offers an appealing way to synthesize high-value chemicals by employing the hydrogen from liquid hydrogen donors rather than H 2 at room temperature. Among the hydrogen carriers, H 2 O is the most striking not only due to its clean and abundant properties and harmless hydroxyl byproduct but also for the high economy of using its easily available isotopic analogues, D 2 O, for deuterated synthesis. We have previously designed P-doped and S-modified Pd and Cu cathodes for electrocatalytic semihydrogenation of alkynes via H 2 O electrolysis, , allowing acceptable compatibility with C–Br, carboxylic acid, and ketone functionalities. However, precise control of the cathodic potential is extremely necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In drug discovery and development, deuteration could improve the pharmacokinetic properties and toxicity of nondeuterated compounds that show great potential for wide application . Since the first deuterated drug Austedo (deutertrabenazine) was approved in 2017, tremendous efforts have been devoted to the discovery of deuterated pharmaceutical analogues. (Hetero) arenes are among the most common skeletons in bioactive molecules and functional natural products. Therefore, it is highly desirable to develop some effective and practical approaches for the preparation of deuterium-labeled compounds. Dehalogenative deuteration of aryl halides has been treated as convenient strategies for the introduction of the deuterium atom onto aromatic rings (Scheme a). Some approaches enabling the transformations of aryl halides to deuterated arenes were reported.…”
Section: Introductionmentioning
confidence: 99%